BROILER CARCASS QUALITY AND SLAUGHTERHOUSE HYGIENE ASSESSMENT IN BLIDA (ALGÉRIA) - Djamila Baazize-Ammi; Redha Djezzar; Karima Benamirouche-Harbi; Nadia Hezil; Seddik Kebbal; Ismail Gharbi; Djamel Guetarni (Agricultura)
The slaughterhouse is where the greatest opportunities for carcass contamination occurs. The present study is a contribution to the evaluation of the hygienic quality of broiler carcasses by evaluating the hygienic state of a modern slaughterhouse (SM) and two traditional slaughterhouses (TS1, ST2) and the impact of good hygiene practices related to premises and slaughtering processes. To do this, a microbiological analysis was carried out by counting total germs, total coliforms and fecal coliforms on 156 surface samples and 30 neck skin samples from chicken carcasses. The results showed for chicken transport cages and the walls a strong contamination at the TS1 level for the microbial groups sought. The carcass contacts surfaces showed contamination for TS1 and TS2 for the microbial groups sought while at the MS level the Fecal coliforms were absent from the Manipulators hands, Knife, carts and Carcass box. Regarding the quality of the carcasses (neck skin), the average contamination for Total aerobic mesophilic is 7,782±0,050 log CFU/g and 4,795±0,034 log CFU/g and 3,545±0,088 log CFU/g average load The Total coliforms is 4,371±0,075 log CFU/g and 2,302±0,184 log CFU/g and 1,593±0,207 log CFU/g for carcasses from TS1, TS2 and MS respectively. For contamination by Fecal coliforms, carcasses from MS showed no contamination, however those from TS1 and TS2 showed an average load of 2,858±0,055 and 1,588±0,156 log CFU/g respectively. Compared to the quality of carcasses from MS, carcasses from ST1 and ST2 were significantly more contaminated (P<0,05). Although there are differences between the modern slaughterhouse and the killings, the main stages of slaughter are similar, however, hygiene strongly conditions the results obtained.